2024
DOI: 10.1093/nar/gkae052
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric structures of DNA ATTTC repeats promoted by divalent cations

Marko Trajkovski,
Annalisa Pastore,
Janez Plavec

Abstract: Structural studies of repetitive DNA sequences may provide insights why and how certain repeat instabilities in their number and nucleotide sequence are managed or even required for normal cell physiology, while genomic variability associated with repeat expansions may also be disease-causing. The pentanucleotide ATTTC repeats occur in hundreds of genes important for various cellular processes, while their insertion and expansion in noncoding regions are associated with neurodegeneration, particularly with sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Previous reports have indicated that i-DNA can fold into an i-motif structure under weakly acidic conditions and low concentrations of divalent cations can stabilize the DNA secondary structure. 50 Here, we observed that the unfolding of all i-DNA into a single strand is aided by a mildly acidic solution with a high concentration of divalent cation electrolytes. Therefore, we deduce that the concentration of divalent cations may potentially affect the unfolding and folding of the i-motif.…”
Section: Effect Of Ionic Charge On the I-motifmentioning
confidence: 90%
“…Previous reports have indicated that i-DNA can fold into an i-motif structure under weakly acidic conditions and low concentrations of divalent cations can stabilize the DNA secondary structure. 50 Here, we observed that the unfolding of all i-DNA into a single strand is aided by a mildly acidic solution with a high concentration of divalent cation electrolytes. Therefore, we deduce that the concentration of divalent cations may potentially affect the unfolding and folding of the i-motif.…”
Section: Effect Of Ionic Charge On the I-motifmentioning
confidence: 90%